Vaalvi [videorecording (DVD)] - Joshi, Swwapnil; Bhave, Subodh; Date-Kelkar, Anita (Movie Time Video, 2024)
Aniket, frustrated with his mentally ill wife Avani's behavior, desires a divorce. Engaged in an affair with dentist Dr. Devika, he plots to end Avani's life. Aniket manipulates Avani into believing his business is failing, and they should both commit suicide to escape their troubles. However, the plan goes awry when Avani's body disappears. Aniket, alarmed, contacts Devika, and they receive an urgent call from Avani's number, adding a mysterious twist to the unfolding events.